Pop-Q Components Comparison among Multiparous and Nulliparous Women - Lisa, Lucy (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To compare the measurement of POP-Q components between multiparous and nulliparous women. Method: This study is a cross-sectional research conducted in several hospitals in Makassar during the period of June to October 2012, with 270 women as the subjects. Subjects were divided into three groups: nulliparous, parity 1-2, and parity 3 (multiparous). We analyzed the mean POP-Q components results between 3 groups using t-test, analysis of prolapse based on POP-Q components measurement, and analysis of correlation between risk factors with prolapse was done using Chi-square test. Result: There is a significant difference in POP-Q components measurement between multiparous and nulliparous women, consecutively for: Aa point -2.14 and -2.97 cm, Ba point -2.11 and -2.99 cm, C point -5.69 and -6.86 cm, gh 3.33 and 2.70 cm, pb 2.60 and 3.27 cm, TVL 8.65 and 9.06 cm, Ap point -2.35 and -2.93 cm, Bp point - 2.61 and -2.96 cm, D point -6.61 and -7.42 cm. In multiparous women, points Aa, Ba, C, D, Ap and Bp became more prolapsed, gh became longer, while pb and TVL became shorter. Conclusion: The proportion of prolapse is higher in multiparous women with significant associations with age, body mass index, education level, and history of heavy physical work, delivering a large baby and use of hormonal contraceptives. [Indones J Obstet Gynecol 2014; 4: 204-210] Keywords: multiparous women, nulliparous women, parity, POP-Q